40.2.19 problem 44

Internal problem ID [6597]
Book : Schaums Outline. Theory and problems of Differential Equations, 1st edition. Frank Ayres. McGraw Hill 1952
Section : Chapter 4. Equations of first order and first degree (Variable separable). Supplemetary problems. Page 22
Problem number : 44
Date solved : Monday, January 27, 2025 at 02:15:01 PM
CAS classification : [[_homogeneous, `class A`], _exact, _rational, _Bernoulli]

\begin{align*} x^{3}+y^{3}+3 x y^{2} y^{\prime }&=0 \end{align*}

Solution by Maple

Time used: 0.003 (sec). Leaf size: 90

dsolve((x^3+y(x)^3)+3*x*y(x)^2*diff(y(x),x)= 0,y(x), singsol=all)
 
\begin{align*} y &= \frac {2^{{1}/{3}} {\left (-\left (x^{4}-4 c_1 \right ) x^{2}\right )}^{{1}/{3}}}{2 x} \\ y &= -\frac {2^{{1}/{3}} {\left (-\left (x^{4}-4 c_1 \right ) x^{2}\right )}^{{1}/{3}} \left (1+i \sqrt {3}\right )}{4 x} \\ y &= \frac {2^{{1}/{3}} {\left (-\left (x^{4}-4 c_1 \right ) x^{2}\right )}^{{1}/{3}} \left (i \sqrt {3}-1\right )}{4 x} \\ \end{align*}

Solution by Mathematica

Time used: 0.226 (sec). Leaf size: 99

DSolve[(x^3+y[x]^3)+3*x*y[x]^2*D[y[x],x]== 0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to \frac {\sqrt [3]{-x^4+4 c_1}}{2^{2/3} \sqrt [3]{x}} \\ y(x)\to -\frac {\sqrt [3]{-1} \sqrt [3]{-x^4+4 c_1}}{2^{2/3} \sqrt [3]{x}} \\ y(x)\to \frac {(-1)^{2/3} \sqrt [3]{-x^4+4 c_1}}{2^{2/3} \sqrt [3]{x}} \\ \end{align*}